SPEC Process III. Synthesis of a Macroporous Silica-Based Crown Ether-Impregnated Polymeric Composite Modified with 1-Octanol and its Adsorption Capacity for Sr(II) Ions and Some Typical Co-Existent Metal Ions - Anyun Zhang; Chunmei Chen; Zhifang Chai; Mikio Kumagai (Adsorption Science & Technology)
A macroporous silica-based 4,4′,(5′)-di(t-butylcyclohexano)-18-crown-6 (DtBuCH18C6)-impregnated polymeric composite, (DtBuCH18C6 + Oct)/SiO 2 -P, was synthesized by molecular modification of DtBuCH18C6 with 1-octanol through hydrogen bonding. This was achieved by impregnating and immobilizing DtBuCH18C6 and 1-octanol molecules in the pores of macroporous SiO 2 -P particles possessing a mean pore diameter of 50 μm. The adsorption of some fission and non-fission products contained in highly active liquid waste (HLW) such as Ru(III), Mo(VI), Pd(II), Na(I), K(I), Cs(I), Sr(II), Ba(II), La(III) and Y(III) onto (DtBuCH18C6 + Oct)/SiO 2 -P was investigated at 298 K. The effects of contact time and HNO 3 concentration within the range 0.1–5.0 M were examined. Increasing the HNO 3 concentration from 0.1 M to 2.0 M led to a significant increase in the adsorption of Sr(II), followed by a decrease when the HNO 3 concentration was increased further to 5.0 M. The optimum concentration of HNO 3 in the adsorption of Sr(II) onto (DtBuCH18C6 + Oct)/SiO 2 -P was determined as 2.0 M. For the other ions examined with the exception of Ba(II), very weak or almost non-existent adsorption capacities were observed at all HNO 3 concentrations. The leaching of total organic carbon (TOC) from (DtBuCH18C6 + Oct)/SiO 2 -P into the aqueous phase was evaluated. Over the HNO 3 concentration range 0.1–3.0 M, the quantity of TOC leached was ca. 40 ppm compared with 355.8–373.3 ppm at HNO 3 concentrations above 4.0 M. Significant reduction of TOC leaching from the macroporous silica-based DtBuCH18C6-impregnated polymeric composite was achieved in 2.0 M HNO 3 . Such behaviour could be of great benefit in using (DtBuCH18C6 + Oct)/SiO 2 -P for the partitioning of Sr(II) from HLW by extraction chromatography.